Use of in situ extracorporeal shock wave lithotripsy in upper ureteric stone - Islam, MS; Rahman, S; Islam, MA; Ahmed, I; Maola, G; Uddin, MM (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):236-8. The abstract of this article is available on the PubMed website